Students View Oral Presentations as Drivers of Speaking Development - Ainur Rohmah Azhari; Dian Novita (Academia Open, 2025)
General Background: English speaking proficiency is a crucial competence for academic communication in foreign language contexts, yet many learners struggle with confidence, vocabulary, and pronunciation when speaking publicly. Specific Background: Classroom oral presentations are widely used to encourage active language use, particularly in bilingual programs where students are expected to communicate in English. Knowledge Gap: Despite their frequent use, limited research has examined students’ perceptions of oral presentations through an integrated cognitive, affective, and conative framework at the junior high school level. Aims: This study explores students’ perceptions of the oral presentation method for developing English speaking ability using Schiffman and Kanuk’s three-component perception model. Results: Findings from semi-structured interviews with four eighth-grade students indicate positive perceptions across all components: cognitively, students reported gains in vocabulary, sentence construction, pronunciation, and idea organization; affectively, initial anxiety gradually shifted into confidence and pride; conatively, students demonstrated strong motivation through deliberate preparation, rehearsal, and preference for presenting in English. Novelty: The study offers a comprehensive perspective by simultaneously examining how students think, feel, and act toward presentation activities rather than focusing solely on skill outcomes. Implications: These findings suggest that oral presentations can serve as a holistic pedagogical strategy that supports linguistic development, emotional readiness, and active learning behavior in English as a foreign language classrooms. Highlights: Learners reported growth in vocabulary use, pronunciation accuracy, and idea organization during classroom tasks. Emotional responses shifted from nervousness to confidence after repeated practice opportunities. Participants showed strong preparation habits, including rehearsal, material mastery, and choosing English for delivery. Keywords: Oral Presentation Method; Speaking Ability; Student Perception; EFL Learners; Junior High School